The long-term safety and effectiveness of the loop technique in left ventricular lead dislocation - Dong, Mengya; Liang, Chenyuan; Cheng, Gong (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Cardiac resynchronization therapy (CRT) is a well-established method that improves the clinical symptoms and long-term prognosis of specific heart failure (HF) patients by restoring systolic synchronicity and enhancing myocardial function. However, the high rate of intraoperative and postoperative left ventricular (LV) lead dislocation limits its application to a great extent. The aim of this study was to demonstrate the long-term safety and effectiveness of a new approach named the loop technique for patients who experience repeated intraoperative transvenous LV lead dislocations during CRT.Methods: The current study was a single-centre, prospective, nonrandomized controlled trial. Fortyfour HF patients who underwent CRT were included. All patients were followed to death or 3 years.Results: Among 44 HF patients, 36 underwent the traditional operation, and 8 underwent the loop technique due to repeated intraoperative LV lead dislocations. Intergroup comparison revealed no significant differences between the two groups with respect to most preoperative indices, intraoperative pacing and sensing parameters. At the end of the 3-year follow-up, 4 (11.1%) patients in the traditional operation group and 2 (25.0%) patients in the loop technique group had died. There was no significant difference in the mortality rate (P=0.30). No complications related to this new technique were observed, such as intracoronary thrombosis, infection or dislocation. Intergroup comparison showed no significant difference in the New York Heart Association (NYHA) class, echocardiography indices, N-terminal pro brain natriuretic peptide (NT-proBNP) level or pacemaker programming parameters.Conclusions: The loop technique is a safe and effective alternative method for patients who experience repeated intraoperative transvenous LV lead dislocations during CRT.